Open Educational Resources in Turkey - Tisoglu, Secil; Kursun, Engin; Cagiltay, Kursat (Springer Singapore, 2020)
The purpose of this study is to present an Open Educational Resources (OER) landscape to the extent of the development (infrastructure, policy, stakeholders and license), integration (curriculum and teaching methodology and resources) and the impact (outcomes) on educational context where each three section holds their sub-sections to provide a comprehensive picture of the OER movement in Turkey. Through the growing trend of movements related to access to, quality of and equity of education, OERs play an important role to reshape the teaching and learning experiences by transforming education in the world. Therefore, beyond the state of the art of OERs in Turkey, how Turkey contributes to this movement is important to share timely. As beginning with the timeline of the initiatives in Turkey, this chapter comprises of three sections within its sub-sections, extent of development, integration and the impact of OERs on education.
Keywords: 4. Education